Reproductive biology of female franciscana dolphins (Pontoporia blainvillei) from Argentina - Panebianco, María Victoria (2015)
The ovaries of 31 franciscana dolphins (19 immature and 12 mature) by-caught in coastal waters of Argentina were examinedto describe the reproductive biology. No ovarian polarity was found, both ovaries were functional and showed similaramounts of corpora. A positive trend was observed between the number of corpora and age (3?8 years old), indicatingthat ovulation scars are detectable for at least 4 years, and a ovulation rate of 0.39 was found for the sampled population.Age, length and weight at sexual maturity were estimated at 3.92+0.09 years, 133.47+ 11.11 cm and 32.68 +2.72 kg,respectively. The annual pregnancy rate was 0.36+0.02 (95% CI ¼ 0.10?0.65). The proportion of lactating and restingfemales found were 0.25 and 0.33 respectively. These outcomes constitute the first reproductive and life history informationon franciscana dolphins from the southernmost population and are important in relation with adequate conservation managementplans for this small cetacean.